Cigarette Sales Promotion Pattern and Smoking Behavior of Sellers in Mulawarman University, Samarinda (Jurnal Ilmu Kesehatan Masyarakat, 2019)
Mulawarman University have the largest number of students in Kalimantan (37,000). This amount has the potential to be smokers supported by the non-realization of non-smoking areas in all faculties and the high circulation of cigarettes through the mobilization of street vendors and retail franchises. The purpose of this study was to find out the dominant factors influencing cigarette sales in the environment of street vendors in Mulawarman University. The design of this study is quantitative research to analyze the correlation between cigarette sales figures, types or brands of cigarettes, attributes and types of cigarette promotion media, knowledge and smoking behavior of street vendors. Statistical analysis on ordinal data using the Spearman analysis test, nominal data using contingency coefficients and ratio data using Pearson analysis. The results of this study are the average cigarette sales per day is 311 cigarettes with the highest cigarette sales is 1760 cigarettes, the type of cigarette promotion media is (55%) banners. The variables that have correlation to cigarette sales are types of cigarette sales places (p = 0.047, R = -0.257); the use of media promotion display (p = 0.002, R = 0.390) and profits from selling cigarettes in rupiah nominal (p = 0.000, R = 0.557). Limiting cigarette promotions around the campus and increasing regulation of non-smoking areas at the maximum is needed. Keywords: Sales promotion, cigarettes, smoking behavior